The Law-Growth Nexus : The Rule of Law and Economic Development - Dam, Kenneth W. (Book collections on Project MUSE., 2006)
"Examines the underlying mechanisms through which the law, judiciary, and legal profession influence the economy. Analyzes enforcement, contracts, and property rights--the concepts collectively defining rule of law--and examines their roles in the real estate and financial sectors. Extended China analysis assesses the importance of the rule of law"--Provided by publisher